As expectativas do ter e o fracasso do ser: representações sociais de adolescência e suicídio entre adolescentes - Silva, Priscilla de Oliveira Martins (2002)
The present work aims to discuss a phenomenon which has been occured often among the adolescent population: the suicide. In the scientific literature there are a few studies that understands that phenomenon in a psychossociological approach, the majority of the studies are focused on the sociological, psychological and psychiatrically approaches. Based on the Theory of Social Representation we analyze the meaning of adolescence and suicide among adolescents and verify the possible relations between these two themes. 360 adolescents of 14 to 23 years old participated in this research; 180 (90 female and 90 male) that live in a urban area and that study in a private school which is located in a neighborhood considered of a high-middle class and high class, and 180 (90 female and 90 male) that live in a rural area and that study in a agrotecnical public school. The results pointed out that the way each group represent the suicide depends on the way they live their adolescence. To the urban area group the social representation of adolescence is configured in two main themes: -party on? and support. The first one means the peer socialization and the second one the parental support. The main concern to this group is being alone. Therefore, the risk factors related to suicide are family problems such as: parental divorce, maltreatment, parental neglect, among others; and problems in relating with others, that can be related to self steam, psychiatric syndromes, among others. The rural area group represents adolescence as a quick transition to adulthood, thus, they are concerned with professional market reality, and not only with loneliness. Therefore the risk factors to these adolescents are the mentioned to the group that live in a urban area and social problems such as: unemployment, low wages, financial difficulties, among others. From the results we conclude that, to have a good adolescent health treatment is indispensable knowing better the adolescents‘ fears, life projects, beliefs, social context in order to provide a effective group of action on that way.